2007
DOI: 10.1001/archneur.64.1.93
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome and Alzheimer Disease

Abstract: Background:The metabolic syndrome is a risk factor for cardiovascular diseases, which have been linked to Alzheimer disease. However, a link between Alzheimer disease and the metabolic syndrome has not yet been established.Objective: To investigate the relationship between the metabolic syndrome and Alzheimer disease.Design, Setting, and Participants: Case-control study of 50 consecutive patients diagnosed with probable Alzheimer disease from the Memory Disorders Clinics, Launceston, Australia, and Bristol, En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(163 citation statements)
references
References 14 publications
4
151
2
6
Order By: Relevance
“…Data concerning age, blood pressure, smoking, and cholesterol level were extracted to generate the FCHDR score, a summary index that was devised to synthesize the combination of different cardiovascular risk factors. 31 This score is especially suitable for the elderly population, which shows several overlapping risk factors, 32 and represents a comprehensive and objective measure to be accounted for in the statistical analyses. The FCHDR calculated for each subject was then used to classify them into the following 3 subgroups according to their cardiovascular risk: low (FCHDR score, Ͻ9%); medium (FCHDR score, 10%-19%); and high (FCHDR score, Ͼ20%).…”
Section: Subjects and Assessment Schedulesmentioning
confidence: 99%
“…Data concerning age, blood pressure, smoking, and cholesterol level were extracted to generate the FCHDR score, a summary index that was devised to synthesize the combination of different cardiovascular risk factors. 31 This score is especially suitable for the elderly population, which shows several overlapping risk factors, 32 and represents a comprehensive and objective measure to be accounted for in the statistical analyses. The FCHDR calculated for each subject was then used to classify them into the following 3 subgroups according to their cardiovascular risk: low (FCHDR score, Ͻ9%); medium (FCHDR score, 10%-19%); and high (FCHDR score, Ͼ20%).…”
Section: Subjects and Assessment Schedulesmentioning
confidence: 99%
“…Several population-based studies suggested that the presence of MetS increased the risk of developing age-related CD, mild cognitive impairment (MCI), AD, and vascular dementia (VaD) [8][9][10][11] and the risk of progression from MCI to dementia [11]. Furthermore, individual components of MetS have been linked to the risk of developing CD and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The report defined MetS as the presence of 3 or more of the following: (i) fasting plasma Several cross-sectional studies have reported 2-to 7-fold increases in the risk of developing cognitive decline [9,10] among those with MetS; nevertheless, other studies have failed to discover an increased risk [11]. Therefore, the association between MetS and the risk of cognitive decline remains unclear.…”
Section: Diagnosis Of Metsmentioning
confidence: 99%